P229 Standardization of Quantum Blue® rapid TDM assays with WHO international standards for adalimumab and infliximab. (27th May 2021) - Afonso, J; Ricken, B; Schuster, T; Guschin, D; Schneider, M
Abstract: Background: Therapeutic drug monitoring of inflammatory bowel disease (IBD) patients under anti-TNF therapy is based on trough level determination of the drug. Rapid assays and multiple ELISAs are available that measure anti-TNF biologics. An international standard is required to improve comparability among different assays. Recently, WHO introduced anti-TNF standards for adalimumab (ADL) and infliximab (IFX). A WHO international reference material (IRM) based standardization is crucial for the harmonization of assays available on the market. Methods: The aim of the study was to standardize the BÜHLMANN Quantum Blue ® ADL and BÜHLMANN Quantum Blue ® IFX based on the WHO IRM for ADL and IFX, respectively. A value transfer from the WHO reference material to the internal calibrator sets for both assays was based on a protocol previously described by Blirup-Jensen et al. (Clin Chem Lab Med 2001; 39(11):1110–1122) and by means of a commercially available ELISA. A method comparison of the ELISA and the rapid test was carried out before the value transfer to guarantee comparability of both assays. Additionally, the correlation of the WHO IRM with the currently used calibrator material was determined for ADL. The correlation of the WHO IFX standard (NIBSC 16/170) with the currently used calibrator material was presented recently (Keller et al. 2020, UEGW 2020). Calibration curves were generated with BÜHLMANN ADL calibrators and with calibrators made from WHO IRM for ADL (NIBSC 17/236). Serum samples, covering a concentration range from 1.0 to 35 µg/mL, were analysed with both calibration curves and compared by Bland-Altman and Passing-Bablok analysis. Results: A preliminary value transfer study revealed an relative uncertainty of 12.3% for both drugs. A good comparison of the ADL and IFX rapid test and the ELISA is given: Passing-Bablok correlation coefficient (R) of 0.953 (ADL) and 0.942 (IFX), and a mean bias determined by Bland-Altman of 1.59 µg/mL (ADL) and -0.5 µg/mL (IFX), respectively. The sample values gained with BÜHLMANN calibrators showed an excellent correlation with values gained with the WHO international standard for ADL as calibrator. Passing-Bablok regression analysis revealed a slope of 1.3 and correlation coefficient (R) of 1.0. Conclusion: To the best of our knowledge, the Quantum Blue ® ADL and Quantum Blue ® IFX, are the first commercially available quantitative lateral flow assays comprising a WHO based standardization. Additionally, it was demonstrated that the current standardizations of Quantum Blue ® ADL correlates very well with the WHO international standard for ADL.